Gêneros da família de reações a texto em uma coleção de livros didáticos de língua portuguesa: estudo na perspectiva sistêmico-funcional da linguagem - Bader Khun, Mhdi Ibrahim (2020)
The general goal of this research is to map text responses family genres in texts in Portuguese language textbooks of the final years of elementary school and the three years of high school. To achieve this goal, it is going to be used the theoretical assumptions of the Systemic Functional Linguistics, with a focus on the Australian perspective over the genres of the text; specifically, of the text responses family (ROTHERY, 1986; ROTHERY, 1993; MARTIN; ROSE, 2008; CHRISTIE; DEREWIANKA, 2008) that, according to Rose and Martin (2012), makes use mainly of the Appraisal semantic-discursive system (MARTIN; WHITE, 2005) to achieve its social purpose. The universe of analysis in this research consists of the volumes of the Português linguagens collection, which was the most distributed by the National Program of the School Textbook in the schooling contexts in which this research was conducted. The collection of the texts was performed after clues of the social purpose of the text responses family, and as an excerpt, texts employed in chapters focusing the subjects of grammar teaching and text interpretation and production were used, constituting the corpus in a total amount of twenty-one texts. The analysis of the linguistic resources of the subsystems attitude and engagement of the Appraisal semantic-discursive system and the description of the schematic genre structure constituted of stages enable to evidence the specific social purpose of each genre. From that, two instantiations of the text genre of personal response were found, eight of the text review genre, one instantiation of the thematic interpretation genre and three instantiations of the genre critical response. Moreover, there were found six texts that instantiate the social purposes of the text responses, but they did not have their schematic genre structure and their specific social purpose described according to the Systemic Functional Linguistics to the present moment, and one text response no it was possible to classify it as a personal answer or review.